Propane oxidative dehydrogenation on VOx/ZrO2 catalysts - Pieck, Carlos Luis (2004)
The catalytic properties of the V2O5/ZrO2 system for the oxidative dehydrogenation of propane were studied. Catalysts with different chemical compositions (i.e., vanadium oxide loadings) were prepared, with activation done by calcination at two temperature levels. Samples were characterized by nitrogen adsorption, temperature-programmed reduction, and Raman and photoelectron spectroscopic techniques. It was found that calcination temperature level strongly affects the structure of ZrO2 (tetragonal zirconia predominates at 500 °C while the transformation to a monoclinic phase occurs at 650 °C). The calcination temperature also affects the nature of vanadium oxide species on the surface of ZrO2. After calcination at 500 °C surface vanadium oxide species are formed at low vanadium loadings, but crystalline V2O5 structures appear at the higher ones. Calcination at 650 °C leads to the formation of ZrV2O7, mainly at high vanadium loadings. The results of propane oxidative dehydrogenation show that surface-isolated vanadium oxide species are more selective to C3H6. On the other hand, it was found that the catalysts suffer a slow deactivation during reaction due to ZrV2O7 formation. This transformation decreases the activity but the activity-selectivity profile is not affected.